2002
DOI: 10.1111/j.1151-2916.2002.tb00108.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Products Obtained during Formation of Barium Monoaluminate through Hydrothermal Precipitation–Calcination Route

Abstract: Nanosized (10 -30 nm particle size) hexagonal barium monoaluminate, having a high surface area of ϳ30 m 2 /g, was synthesized by calcination of hydrothermally prepared precursors. The precursors were obtained by hydrolytic precipitation, using a mixed solution of barium and aluminum nitrates in the presence of aqueous urea at 180°C. Based on the results of XRD, FTIR, SEM/EDS, TEM, and TG-DTA studies, the most probable sequence of reactions leading to the formation of barium monoaluminate was (i) conversion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 25 publications
(31 reference statements)
1
1
0
Order By: Relevance
“…No crystalline phase of any metastable aluminum oxides were found in these samples. In a previous study on barium mono-aluminate, similar amorphous forms of Al-oxide/hydroxides were observed [11] after calcination at 800 jC. In all the XRD patterns, main peak of maximum intensity for BaCO 3 was observed for 2h varying between 23.55j and 23.96j, while the other major peak at 24.22j was not observed even when the main peak had 100% relative intensity.…”
Section: Xrd Analysis Of 800 Jc Calcined Samplessupporting
confidence: 52%
“…No crystalline phase of any metastable aluminum oxides were found in these samples. In a previous study on barium mono-aluminate, similar amorphous forms of Al-oxide/hydroxides were observed [11] after calcination at 800 jC. In all the XRD patterns, main peak of maximum intensity for BaCO 3 was observed for 2h varying between 23.55j and 23.96j, while the other major peak at 24.22j was not observed even when the main peak had 100% relative intensity.…”
Section: Xrd Analysis Of 800 Jc Calcined Samplessupporting
confidence: 52%
“…In addition, the combination of SiO 2 and Al 2 O 3 with CaO, MgO, Cr 2 O 3 and/or BaO is commonly employed to impart specific properties related to phase formation, sintering temperature, porosity, resistance to chemical attack or thermal shock, wettability, etc. (Allahevrdi et al, 1998;Mishra et al, 2002). During sintering, kaolinite is transformed into meta-kaolin with a highly disordered structure due to dehydroxylation and subsequent reorganization (Bundy, 1993;Chandrasekhar & Ramaswamy, 2002).…”
mentioning
confidence: 99%